HPI Perspective Child Abuse Analysis - Muhammad Ridho Siregar (IAIN Padangsidimpuan, 2022)
This research is backgrounded by the crime of obscenity against minors who have not reached the age of 18 years, such as the case that occurred at Batu Rusa Beach, Tabuyung Village, Muara Batang Gadis District, Mandailing Natal Regency. The repeated obscenity of two of his stepsons, in this case, the prosecutor charged him with imprisonment for 11 years and a fine of Rp. 100,000,000, while the judge sentenced him to imprisonment for 13 years and a fine of Rp. 100,000,000. The formulation of the problem in this study is how the judges consider in imposing criminals in the decision of the Mandailing Natal District Court number 2 / Pid.Sus / 2021 / PN.Mdl, How is the review of Islamic Criminal Law against the decision of the Mandailing Natal District Court number 2 / Pid.Sus / 2021 / PN.Mdl. The purpose of this study is to find out the judge's consideration in imposing a criminal in the decision of the Mandailing Natal District Court number 2 / Pid.Sus / 2021 / PN.Mdl, This research uses a descriptive qualitative method, namely research conducted to find out and study intensively the background of circumstances, community conditions, interactions of individuals, groups, institutions, and social groups. The data collection techniques used in this study are interviews, and documentation. The results of the study stated that the judge's consideration in decision number 2/Pid.Sus/2021/PN.Mdl was appropriate according to juridical and non-juridical considerations. The judge's consideration in decision number 2/Pid.Sus/2021/PN.Mdl according to the Islamic Criminal Law, the punishment that has been determined by the panel of judges is in accordance with the Islamic Criminal Law, namely ta'zir which in this case is the one with regard to independence in the form of imprisonment for 13 (thirteen) years and a fine of Rp. 100,000,000.00 (one hundred million rupiah) provided that if the fine is not paid, it will be replaced by imprisonment for 6 (six) months.